Ludzkie ciało jako holobiont i hybryda: szkic z zakresu etnografii wielogatunkowej - Kozhevnikova, Magdalena (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2022)
This text treats a body as a holobiont, i.e. an organism composed of many entities that together contribute to the functioning of the whole. French biologist Marc-André Selosse postulates that the holobiont concept replaces the obsolete notion of the separateness of the organism. A human spends the individual and social life in a network of relationships and interdependencies with other organisms, both inside and outside the body. Therefore, human social interaction can be viewed as the interaction of many different entities. In turn, biotechnology made possible human hybridization – the creation in laboratory conditions of organisms that at the genetic level combine the traits of humans and other animals, as well as transgenic organisms and “mosaics” consisting of cells, tissues or organs of different types. Basically, this scientific activity pursues therapeutic goals (xenotransplantation and organ cultivation, laboratory modeling, drug production, etc.). The implications of these actions, as well as the deepening knowledge of species interdependence, raise questions about the real value and validity of species classification: we also need to re-examine such issues as body boundaries, the role of hygiene, and body ethics and aesthetics. Biological sciences are becoming an important source (not only stricte biological) of knowledge about humans and their environment, it becomes necessary to take into account their achievements in the humanitarian sphere. This results in a non-anthropocentric anthropology that builds and shapes a new view of interspecies relationships, also within organisms. This text is conceived as a voice in the ever-expanding debate about posthuman and post-anthropology.
24 cm
Keywords: etnografia -- czasopisma; body; holobiont; hybrid; posthumanism; non-antropocentric anthropology; interspecies ethics; microorganisms; multispecies ethnography